A new discourse on spirituality in public education. Confronting the challenges in a post-secular society. Issue 1 (2nd January 2016) - Natsis, Eva
Abstract: Australia is facing a new frontier in the educational discourse of spirituality as we transition into a globalised and post-secular society. Teachers are now faced with the question of how to respond to the intrinsic spiritual awareness of secondary school students and the subsequent inquiry process into matters of personal spirituality, meaning and worldview. In Independent and Catholic schools across Australia, spirituality has a dimension to learning and has a significant place in the curriculum and in the classroom, inculcated through pastoral care programmes and the teaching of religious education. However, in public schools, there is a paucity of research investigating whether young people consider spirituality to be an important and worthwhile component of their educational experience. This article highlights the importance of inquiry into spirituality in public education, through political discourse, and the potential for resurgence in exploring spiritual lived experience from a phenomenological perspective.